-Islamic features in the Poem of Al–furqan’ month For the Poet Mohammad Al - Majzoub- A literary Study - al-Qathami, Safir bin Khalaf bin Mtaib (Journal of Humanities & Social Sciences, 2018)
This research addresses "Shahr Al-Furqan" poem by Muhammad Al-Majdhub, May Allaah bestow mercy on him, with the aim to highlight the Islamic features it contains, adopting the technical analytical methodology according to the following steps: After the introduction, I stated the text of the poem, gave a biography of the poet and highlighted the Islamic features in it. That was followed by a conclusion that involved the research summary and prominent findings. While studying this text, I could discover that it was greatly influenced by Islam as the features of this influence clearly and greatly manifest in its theme, form and content. The theme is one of the Islamic themes and its form was impacted in the aspect of diction (words and expression), rhetorical styles, where the text contained some Islamic terms and expressions and some rhetorical styles derived from Islam. The text content beats with vibrant Islamic spirit because its meanings and concepts are derived from the noble Qur’an, the Prophetic tradition (Hadith) and Muslim reality. Its emotion is that of Islam because it was composed for Islam bearing its blessed whiffs. Thus, the text came replete with sincere spiritual emotions towards the month of Ramadan and its associated religious activities and occasions. Some of the glaring findings of the study include the following: 1- Islam’s deep influence on the poet in the theme and concepts born by his text in form and content. 2- Elucidation of Islamic features of literary texts unveils many Islamic values and enhances them in the minds. 3- Being influenced by Islam and deriving meanings from its sprouting fountain of wisdom by an able literary guru enhances the value of his literary work and renders it acceptable to the reader.